SUBSTITUSI TEPUNG ALMOND DENGAN TEPUNG KEMIRI (Aleurites moluccana Wild) TERHADAP KARAKTERISTIK KULIT MACARON - Adnyasuari, Ida Ayu Ganitri; Ekawati, I Gusti Ayu; Hapsari Arihantana, Ni Made Indri (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2019)
This research aims to identify the substitution of almond flour with candlenut flour on the characteristics of macaron shell, and to identify the right concentration of almond flour with candlenut flour on the characteristics of macaron shell. This research used randomized block design with the treatment ratio of almond flour with candlenut flour, which consists of 6 levels such as: 100% : 0%, 80% : 20%, 60% : 40%, 40% : 60%, 20% : 80%, and 0% : 100%. Each treatment was repeated 3 times, resulting in 18 experimental units. The data were then analyzed using Analysis of Variance and if the treatment had an effect on the parameter, the Duncan test was performed. The result showed that substitution of almond flour with candlenut flour had a significant effect on water content, ash content, protein content, fat content, carbohydrate content, swelling, flavor (hedonic), texture (hedonic), taste (scoring) and overall acceptance (hedonic). Substitution of almond flour with candlenut flour 40% had the best characteristics, with 2,40% water content, 2,51% ash content, 9,40% protein content, 18,98% fat content, 66,70% carbohydrate content, 130,81% swelling, color, flavor, taste, and overall acceptance liked, taste candlenut medium and texture very soft.